2020
DOI: 10.1519/jsc.0000000000003768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training at Different Loads on Inflammatory Biomarkers, Muscle Mass, Muscular Strength, and Physical Performance in Postmenopausal Women

Abstract: Carneiro, MAS, de Oliveira Júnior, GN, de Sousa, JFR, Murta, EFC, Orsatti, CL, Michelin, MA, Cyrino, ES, and Orsatti, FL. Effects of resistance training at different loads on inflammatory biomarkers, muscle mass, muscular strength, and physical performance in postmenopausal women. J Strength Cond Res 36(6): 1582–1590, 2022—It has been suggested that the effect of resistance training (RT) on circulating proinflammatory biomarkers may be dependent on muscle mass gain. A few recent studies have suggested that low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Parallel to this, 10-15RM allowed for performing more repetitions (see Table 1). Notably, higher RT volume frequently results in greater gains in muscle mass (12,35). Therefore, this factor may have contributed to the superiority in SMM gains elicited by lower load over the higher load group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel to this, 10-15RM allowed for performing more repetitions (see Table 1). Notably, higher RT volume frequently results in greater gains in muscle mass (12,35). Therefore, this factor may have contributed to the superiority in SMM gains elicited by lower load over the higher load group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more divergence has emerged, indicating that lower-load (30–35RM) may be more effective for increasing SMM than higher-load (8–12RM) while promoting similar muscular strength gains in older women after 12 wk of RT (12). Also, no difference in muscular strength and SMM was found after 8 wk of RT in moderate and low load (10RM vs 15RM) in older women (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several different mechanisms may link these two conditions, such as menopause, in ammatory activity, oxidative stress, malabsorption, malnutrition, excessive ubiquitin-proteasome system activation a lack of physical activity, apoptosis, endothelial dysfunction, and poor muscle blood ow [6,11,15]. Menopause may be a particularly important mediator of the interplay between sarcopenia and HF, given that several reports have shown that reductions in estrogen levels are associated with the marked augmentation of the production of pro-in ammatory cytokines such as TNF-a, IL-4, IL-10, and IL-12, in turn enhancing visceral adiposity and reducing both muscle strength and muscle mass, increasing the risk of cardiovascular events and CHF [19,20]. Estrogens are also natural antioxidants, and the loss of estrogen production as a consequence of menopause thus contributes to the establishment of persistent oxidative stress which may contribute to more severe muscle atrophy and higher rates of cardiovascular events [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The load intensity used in the first set of each exercise allowed individuals to perform between 27 (minimal) and 31 (maximum) repetitions (LL) or 8 (minimal) and 12 (maximum) repetitions (HL). The weight in each exercise was adjusted by 5% to 10% when the upper limit of the repetition zone was reached in the first set (LL = 31 repetitions and HL = 12 repetitions) (34)(35)(36).…”
Section: Methodsmentioning
confidence: 99%